Endoscopic Management of Weight Recurrence Following Bariatric Surgery - Abboud, Donna Maria; Yao, Rebecca; Rapaka, Babusai; Ghazi, Rabih; Ghanem, Omar M.; Abu Dayyeh, Barham K. (Frontiers in Endocrinology, 2022)
Metabolic and bariatric surgery is the most effective therapy for weight loss and improving obesity-related comorbidities, comprising the Roux-en-Y gastric bypass (RYGB), gastric banding, sleeve gastrectomy (SG), and biliopancreatic diversion with duodenal switch. While the effectiveness of weight loss surgery is well-rooted in existing literature, weight recurrence (WR) following bariatric surgery is a concern. Endoscopic bariatric therapy presents an anatomy-preserving and minimally invasive option for managing WR in select cases. In this review article, we will highlight the endoscopic management techniques for WR for the most commonly performed bariatric surgeries in the United States –RYGB and SG. For each endoscopic technique, we will review weight loss outcomes in the short and mid-terms and discuss safety and known adverse events. While there are multiple endoscopic options to help address anatomical issues, patients should be managed in a multidisciplinary approach to address anatomical, nutritional, psychological, and social factors contributing to WR.